POLA PENDIDIKAN BERBASIS MUATAN KEBENCANAAN DI SEKOLAH PERENCANAAN - , RUD NOKEO AL KINDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the urgency of the problem of substance disaster on disaster planning paradigm into consideration in planning the school environment, and formulate disaster Payload Pattern-Based Education as currently practiced in the area of planning schools in Indonesia. To achieve the objectives of this research uses an inductive approach to qualitative research and descriptive research. Data was collected by the method of literature studies: best practices and lessons learned, interviews are used to explore existing data as a representation of education that in fact already done in school planning in Indonesia, and triangulation with experts and observation of data in an effort to enrich, enhance and demonstrate the objectivity of this research . Based on the charge of disaster planning is built in each school, have different characteristics and peculiarities. The emphasis in creating a new understanding associated with different approaches. Although ideally the same concept of disaster but variations of meaning and approach with specialization researchers also creates different meanings and associations. Charge at the school disaster planning into partial patterns in the compulsory subjects include: introduction to disasters, instruments and risk budgeting, the concept of resilience, comunity awareness, concepts of uncertainty, risk mapping with GIS optimization, software development, and the area affected by the rule evacuation, disaster as a main issue in the studio and planning process, as well as creating a space with an understanding of disaster as an object of study. Some of the more specific subject of study area based on studies and planning schools as elective courses: (1) recilience city as a charge close to urban design and planning theory